Lectotypification of the taxa of Adolpho Ducke from the Brazilian Amazon - Leal, E. D.; Da Costa, D. P.; Forzza, R. C. (Phytotaxa, 2010)
Adolpho Ducke was one of the most important Brazilian botanists during the first half of the 20th Century, dedicating more than 50 years to collecting, cataloguing and identifying of the Amazonian flora. The majority of his collections are deposited at the herbaria of the Museu Paraense Emilio Goeldi (MG) and Rio de Janeiro Botanical Garden (RB). The latter contains about 1,500 types collected by Ducke and amongst them, around 900 taxa are described by him. In many of his publications he did not clearly indicate a holotype. The present work discusses the lectotypification of 23 names published by Ducke.